Tightly-Secure Authenticated Key Exchange - Bader, Christoph; Hofheinz, Dennis; Jager, Tibor; Kiltz, Eike; Li, Yong (Theory of Cryptography - 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part I)

Comprehensive Service Matching with MatchBox - Börding, Paul; Bruns, Melanie; Platenius, Marie Christin (10th Joint Meeting of the European Software Engineering Conference and the ACM SIGSOFT Symposium on the Foundations of Software Engineering (ESEC/FSE'15))
Nowadays, many service providers offer software components in the form of Software as a Service. Requesters that want to discover those services in order to use or to integrate them, need to find out which service satisfies their requirements best. For this purpose, service matching approaches determine how well the specifications of provided services satisfy their requirements (including structural, behavioral, and non-functional requirements). In this paper, we describe the tool-suite MatchBox that allows the integration of existing service matchers and their combination as part of flexibly configurable matching processes. Taking requirements and service specifications as an input, MatchBox is able to execute such matching processes and deliver rich matching results. In contrast to related tools, MatchBox allows users to take into account many different kinds of requirements, while it also provides the flexibility to control the matching process in many different ways.

Competition and Product Innovation of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen
On an intermediate goods market we allow for vertical and horizontal product differentiation and analyze the influence of simultaneous competition for resources and customers on the market outcome. Asymmetries between intermediaries cannot arise just from distinct product qualities, but also from different production technologies. The intermediaries face either price or quantity competition on the output market and a monopolistic input supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Considering product innovation for symmetric productivities we derive equilibrium conditions on the investment costs and compare price and quantity competition. It turns out that on the one hand there exist product qualities and degrees of horizontal product differentiation for complements such that asymmetric investment equilibria fail to exist. On the other hand we find that there also exist product qualities and degrees of horizontal product differentiation for substitutes such that existence can be guaranteed if the investment costs are chosen accordingly.

Combining Service-oriented Computing with Embedded Systems - A Robotics Case Study - Jungmann, Alexander; Jatzkowski, Jan; Kleinjohann, Bernd (Proceedings of the 5th IFIP International Embedded Systems Symposium)
In this paper, we introduce an approach for combining embedded systems with Service-oriented Computing techniques based on a concrete application scenario from the robotics domain. Our proposed Service-oriented Architecture allows for incorporating computational expensive functionality as services into a distributed computing environment. Furthermore, our framework facilitates a seamless integration of embedded systems such as robots as service providers into the computing environment. The entire communication is based on so-called recipes, which can be interpreted as autonomous messages that contain all necessary information for executing compositions of services.

Budget Games with priced strategies - Pautz, Jannis

Temporal plans for software architecture reconfiguration - Ziegert, Steffen; Wehrheim, Heike (Computer Science - R & D)

From Program Verification to Time and Space: The Scientific Life of Ernst-Rüdiger Olderog - Meyer, Roland; Wehrheim, Heike (Correct System Design - Symposium in Honor of Ernst-Rüdiger Olderog on the Occasion of His 60th Birthday, Oldenburg, Germany, September 8-9, 2015. Proceedings)

Verifying Opacity of a Transactional Mutex Lock - Derrick, John; Dongol, Brijesh; Schellhorn, Gerhard; Travkin, Oleg; Wehrheim, Heike (FM 2015: Formal Methods - 20th International Symposium, Oslo, Norway, June 24-26, 2015, Proceedings)

TSO to SC via Symbolic Execution - Wehrheim, Heike; Travkin, Oleg (Hardware and Software: Verification and Testing - 11th International Haifa Verification Conference, HVC 2015, Haifa, Israel, November 17-19, 2015, Proceedings)

Correct System Design - Symposium in Honor of Ernst-Rüdiger Olderog on the Occasion of His 60th Birthday, Oldenburg, Germany, September 8-9, 2015. Proceedings

Bewertung von Renderingalgorithmen für komplexe 3-D-Szenen - Jähn, Claudius

Automatic Service Discovery and Composition for heterogeneous service partners - Huma, Zille

Automated Online Service Composition - Mohr, Felix; Jungmann, Alexander; Kleine Büning, Hans (Proceedings of the 12th IEEE International Conference on Services Computing (SCC))
Services are self-contained and platform independent software components that aim at maximizing software reuse. The automated composition of services to a target software artifact has been tackled with many AI techniques, but existing approaches make unreasonably strong assumptions such as a predefined data flow, are limited to tiny problem sizes, ignore non-functional properties, or assume offline service repositories. This paper presents an algorithm that automatically composes services without making such assumptions. We employ a backward search algorithm that starts from an empty composition and prepends service calls to already discovered candidates until a solution is found. Available services are determined during the search process. We implemented our algorithm, performed an experimental evaluation, and compared it to other approaches.

On the Complexity of Fundamental Problems in Dynamic Ad-hoc Networks - Abshoff, Sebastian

Glycemic index, glycemic load and glycemic response: An International Scientific Consensus Summit from the International Carbohydrate Quality Consortium (ICQC) - Augustin, L.S.A.; Kendall, C.W.C.; Jenkins, D.J.A.; Willett, W.C.; Astrup, A.; Barclay, A.W.; Björck, I.; Brand-Miller, J.C.; Brighenti, F.; Buyken, Anette; Ceriello, A.; La Vecchia, C.; et al. (Nutrition, Metabolism and Cardiovascular Diseases)

DUC - Fostering Diversity Aspects in Higher Education by eLearning and User generated Content - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Rechuel, R. (Proceedings of E-LEARN 2015 - World Conference on E-Learning)

Behavioral Mechanisms Prompted by Virtual Rewards: The Small-Area Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the 23rd European Conference on Information Systems (ECIS))

Fatty acid supply with complementary foods and LC-PUFA status in healthy infants: results of a randomised controlled trial - Libuda, Lars; Mesch, Christina M.; Stimming, Madlen; Demmelmair, Hans; Koletzko, Berthold; Warschburger, Petra; Blanke, Katharina; Reischl, Eva; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

Short-term effects of lunch on children's executive cognitive functioning: The randomized crossover Cognition Intervention Study Dortmund PLUS (CogniDo PLUS) - Schröder, Maike; Müller, Katrin; Falkenstein, Michael; Stehle, Peter; Kersting, Mathilde; Libuda, Lars (Physiology & Behavior)

Interactions in IS Project Portfolio Selection: Status Quo and Perspective - Müller, M.; Meier, Christian; Kundisch, Dennis; Zimmermann, Steffen (Wirtschaftsinformatik Proceedings)